2017
DOI: 10.1590/1676-0611-bn-2016-0281
|View full text |Cite
|
Sign up to set email alerts
|

Diet of two syntopic species of Crenuchidae (Ostariophysi: Characiformes) in an Amazonian rocky stream

Abstract: This study assessed the diet of two poorly known syntopic fish species of the family Crenuchidae, Characidium aff. declivirostre and Leptocharacidium omospilus, in a Presidente Figueiredo´ rocky stream, Amazonas, Brazil. The stomach contents were analyzed and their Frequency of Occurrence (FO %) and Relative Volume (Vol %) were combined in a Feeding Index (IAi). We examined 20 individuals of C. aff. declivirostre and 23 of L. omospilus. The Morisita-Horn Index was used to estimate the overlap between the diets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(26 reference statements)
1
1
0
2
Order By: Relevance
“…Dietary and spatial resources are primary drivers of species' coexistence in vertebrates (Schoener 1974) and several studies present evidences of habitat segregation in Neotropical stream fishes (Brejão, Gerhard, and Zuanon 2013;Silva et al 2016;Soares et al 2017;Ferreira et al 2021). On the other hand, Ross (1986) suggested that food partitioning is more important than spatial segregation in fishes, which is supported for some Neotropical fish assemblages (Brazil-Sousa, Marques, and Albrecht 2009;Fernandes et al 2017;Barili et al 2011;Correa and Winemiller 2014). Our results highlight that the most important traits favoring spatial and trophic partitioning covary in Amazonian stream fishes, hence being both equally important for potential niche partitioning.…”
Section: Discussionsupporting
confidence: 63%
“…Dietary and spatial resources are primary drivers of species' coexistence in vertebrates (Schoener 1974) and several studies present evidences of habitat segregation in Neotropical stream fishes (Brejão, Gerhard, and Zuanon 2013;Silva et al 2016;Soares et al 2017;Ferreira et al 2021). On the other hand, Ross (1986) suggested that food partitioning is more important than spatial segregation in fishes, which is supported for some Neotropical fish assemblages (Brazil-Sousa, Marques, and Albrecht 2009;Fernandes et al 2017;Barili et al 2011;Correa and Winemiller 2014). Our results highlight that the most important traits favoring spatial and trophic partitioning covary in Amazonian stream fishes, hence being both equally important for potential niche partitioning.…”
Section: Discussionsupporting
confidence: 63%
“…Os igarapés de primeira ordem são sistemas alóctones muito dependentes das matas ripárias que servem como fonte de energia e nutrientes (KAWAGUCHI et al, 2003). Essa dependência já vem sendo descrita em vários trabalhos (ANJOS, 2005;SANTOS et al, 2015, FERNANDES et al, 2017. O estudo de Anjos ( 2005) descreve que as famílias Characidae, Lebiasinidae são sempre representativas nas categorias dos insetos alóctones, o que foi corroborado no presente estudo.…”
Section: Discussionunclassified
“…Em riachos rochosos na Amazônia, Characidium aff. declivirostre (Characiformes, Crenuchidae) e Leptocharacidium omospilus (Characiformes, Crenuchidae) se alimentaram de larvas e pupas de Chironomidae, Hydroptilidae, Hydropyschidae e Pyralidae (Fernandes et al 2017), indicando comportamento de procura junto ao fundo e a tática do tipo "senta-e-espera", empregadas por espécies do gênero Characidium (Aranha et al 1998). Por outro lado, hábitos mais especializados, como herbivoria e piscivoria foram pouco relatados para as diferentes bacias consideradas, sendo essas guildas mais comuns na bacia Amazônica.…”
Section: Guildas Tróficasunclassified